Why Online Dynamic Mesh Refinement is Better for Parallel Climatological Models - Schepke, Claudio; Maillard, Nicolas; Schneider, Joerg; Heiss, Hans-Ulrich (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2011: Anais do XXIII International Symposium on Computer Architecture and High Performance Computing, 2011)
Forecast precisions of climatological models are limited by computing power and time available for the executions. As more and faster processors are used in the computation, the resolution of the mesh adopted to represent the Earth's atmosphere can be increased, and consequently the numerical forecast is more accurate and shows local phenomena. However, a finer mesh resolution, able to include local phenomena in a global atmosphere integration, is still not possible. To overcome this situation, different mesh refinement levels can be used at the same time for different areas. In this context, this paper evaluates how mesh refinement at run time can improve performance for climatological models. In order to contribute with this analysis, an online dynamic mesh refinement was developed. It increases mesh resolution in parts of a parallel distributed model, when special atmosphere conditions are registered during the execution. The results show that the parallel execution of this improvement provides better resolution for the meshes, without a significant increase of execution time.